Cases of tuberculous pleurisy in sarcoidosis patients - N. A. Stogova (Туберкулез и болезни лёгких)
The article describes 3 clinical cases of tuberculous pleurisy in pulmonary sarcoidosis patients who received courses of glucocorticosteroid therapy in the past. In all cases, the tuberculous etiology of pleurisy was confirmed by microbiological detection of the pathogen in exudate or biopsy specimens.